Evaluation of gastric polyps detected by endoscopy: A single-center study of a four-year experience in Turkey - Atalay, Roni; Solakoğlu, Tevfik; Özer Sarı, Sevil; Köseoğlu, Hüseyin; Akın, Fatma Ebru; Demirezer Bolat, Aylin; Selvi, Eyüp; Şemnur Büyükaşık, Naciye; Ersoy, Osman (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The aim of this study was to evaluate the gastric polyps detected by endoscopy in our institution with respect to their frequency, size, anatomic location, presence of dysplasia, and histopathologic features. Materials and Methods: Records of a total of 14,240 patients who underwent endoscopy between January 2008 and January 2012 were reviewed retrospectively. Of the 14,240 patients, 174 determined to have at least 1 histopathologically proven polyp were included in the study. Results: Three hundred eleven gastric polyps were found in 174/14,240 (1.2%) patients (1.79 polyps per patient). Gastric polyps were found most commonly in the antrum (41.5%). Of all gastric polyps, 189 (60.8%) were less than 1 cm. Histopathologically, the most common polyp type was hyperplastic (n: 261, 83.9%), followed by adenomatous (n: 23, 7.4%). Eight (34.8%) of the adenomatous polyps showed dysplasia, and in 4 (17.4%) of these cases, the dysplasia was high-grade. Nineteen (6.1%) of all gastric polyps were identified to be fundic gland polyps. Conclusion: According to this study from Turkey, the majority of polyps detected by endoscopy was solitary, smaller than 1 cm, and found in the antrum; furthermore, the most common type was a hyperplastic polyp.